Gestational gigantomastia complicated with mastitis - Teixeira, Calina Maria Loures de Oliveira; Lopes, Carolina Teixeira de Assis; Resende, Isadora Senra de Souza; Carmo, Patricia Oliveira; Daroda, Romeu Ferreira; Reis, Tulio Gonçalves (Mastology, 2020)
Gestational gigantomastia (GG) is a disease defined by rapid and disproportionate breast enlargement in pregnancy. Its complications may lead to emergency mastectomy or induced miscarriage. We present a case report in which pregnancy had a favorable evolution after the surgical intervention of the breasts.